Ecohydrology: A New Interdisciplinary Approach to Investigate on Climate-Soil- Vegetation Interactions - Manfreda, Salvatore (Annals of Arid Zone, 2016)
Society is facing growing environmental problems that require new research efforts to understand the way ecosystems operate and survive and their mutual relationships with the hydrologic cycle. This is fundamental to advance predictive models used by researchers, industry, and environmental managers. In this frame, ecohydrology faces this task with the aim to provide improved forecasting and mitigation of flood and drought risk, better understanding of implications of land use changes on terrestrial ecosystems (such as'deforestation or desertification), improved weather and climate predictions, better comprehension of climatic changes effects on terrestrial ecosystems. The scope of the present paper is to address the most challenging questions of ecohydrology providing a review of some of the most recent results in this emerging field. Key words: Ecohydrology, climate-soil-vegetation, soil moisture, vegetation patterns.